French policy towards the barbarian tribes In Morocco, Al-Aqsa 1930-1937 (Journal of the College of Basic Education, 2022)
Al-Aqsa Morocco has maintained its independence under the Alawi rule and for long historical periods, but this independence did not last because the eyes of European countries were directed towards Al-Aqsa Morocco, and then these countries competed for the purpose of controlling it and obtaining privileges.These countries concluded many agreements among themselves, which sought to consolidate their presence in this country. France was the most interested European country in this country, for reasons related to its geographical location, in addition to its desire to strengthen its presence in North Africa, especially after its control of Algeria.